Malaria Vectors in Ecologically Heterogeneous Localities of the Colombian Pacific Region - Naranjo-Díaz, Nelson (Public Library of Science, 2014)
The Colombian Pacific region is second nationally in number of malaria cases reported. This zone presents great ecological heterogeneity and Anopheles species diversity. However, little is known about the current spatial and temporal distribution of vector species. This study, conducted in three ecologically different localities of the Pacific region, aimed to evaluate the composition and distribution of Anopheles species and characterize transmission intensity. A total of 4,016 Anopheles mosquitoes were collected representing seven species. The composition and dominant species differed in each locality. Three species were infected with malaria parasites: Anopheles darlingi and An. calderoni were infected with Plasmodium falciparum and An. nuneztovari with Plasmodium vivax VK210 and VK247. Annual EIRs varied from 3.5–7.2 infective bites per year. These results confirm the importance of the primary vector An. nuneztovari in areas disturbed by human interventions, of An. darlingi in deforested margins of humid tropical rainforest and An. albimanus and the suspected vector An. calderoni in areas impacted by urbanization and large-scale palm oil agriculture close to the coast. This constitutes the first report in the Colombia Pacific region of naturally infected An. darlingi, and in Colombia of naturally infected An. calderoni. Further studies should evaluate the epidemiological importance of An. calderoni in the Pacific region.